On *-measure monads on the category of ultrametric spaces - Sukhorukova, Kh.O.; Zarichnyi, M.M. (Carpathian Mathematical Publications, 2022)
The functor of *-measures of compact support on the category of ultrametric spaces and non-expanding maps is introduced in the previous publication of the authors. In the present note, we prove that this functor determines a monad on this category. The monad structure allows us to define the tensor product of *-measures. We consider some applications of this notion to equilibrium theory.